BIODIVERSITAS MAKROFUNGI DI SEKITAR KAWASAN CURUG LEUWI MANGROD, KABUPATEN SERANG, BANTEN: DESKRIPSI DAN POTENSI PEMANFAATAN - Anzelina Tristina; Nurul Fitiriani; Syifa Auliya Zulfah; Nani Maryani; Rida Oktorida Khastini (Jurnal Biolokus: Jurnal Penelitian Pendidikan Biologi dan Biologi, 2022)
Fungi are found widely in tropical areas throughout the world, including Indonesia. Banten Province is estimated to have a high diversity of macrofungi. This study aims to explore and describe the morphological characteristics of macrofungi and their potential use in the area of Curug Leuwi Mangrod Cibojong, Padarincang, Serang Regency, Banten. The research was conducted in September - October 2021 using the cruising method. A total of 10 species of macrofungi consisting of 1 species of the Ascomycota division and 9 species of the Basidiomycota division were found around the waterfall from various substrates, both on the soil surface and on rotten tree trunks. A total of 3 species were found to be potential sources of food, 9 species had the potential to be used as medicinal ingredients. Information on the diversity and potential use of macrofungi can be used as a basis for further macrofungi development.